Evaluation of a classroom movement integration training delivered in a low socioeconomic school district. (April 2019) - Stewart, Gregory; Webster, Collin A.; Weaver, R. Glenn; Stodden, David F.; Brian, Ali; Egan, Cate A.; Michael, Robert Dan; Sacko, Ryan; Patey, Matthew
Highlights: A movement integration training delivered to an elementary school was evaluated. The training lacked fidelity to recommendations for professional development. School professionals had varied perceptions of the training's purpose. School professionals discussed challenges and future recommendations. Abstract: Movement integration (MI), which involves infusing physical activity (PA) into general education classrooms, is an evidence-based strategy within whole-of-school approaches for helping children meet the national PA guideline of at least 60 min per day. This study evaluated an MI training delivered in a low socioeconomic elementary school that had recently invested in three movement facilitative classrooms (a kinesthetic classroom and two activity labs). We investigated (a) the training's fidelity in meeting recommended best practices for professional development and (b) school professionals' perspectives of the training. Eight school professionals participated in the study, including five classroom teachers, two activity lab supervisors, and the principal. The researchers used a video of the training to rate the fidelity of the training to best practice recommendations. Interviews, field notes, and informal conversations with participants were qualitatively analyzed for themes. The training received a total fidelity score of 42%. Qualitative findings highlighted participants' varied perspectives of the training's purpose, challenges associated with the training and future recommendations for MI trainings. For MI trainings to be a valuable asset in increasing teachers' value and effective implementation of MI, trainings need to be designed to be in line with best practice recommendations and teachers' perceived needs.